Exchange rate misalingment estimates: Sources of differences - Yin-wong Cheung; Eiji Fujii (Center for Economic Studies and ifo Institute (CESifo), 2011)
We study the differences of currency misalignment estimates obtained from alternative datasets derived from two International Comparison Program (ICP) surveys. A decomposition exercise reveals that the year 2005 misalignment estimates are substantially affected by the ICP price revision. Further, we find that differences in misalignment estimates are systematically affected by a country's participation status in the ICP survey and its data quality - a finding that casts doubt on the economic and policy relevance of these misalignment estimates. The patterns of changes in the estimated degree of misalignment across individual countries, as illustrated by the BRIC economies, are quite variable.
Keywords: F31; F41; E01; C31; 330; Penn Effect Regression; data revision; PPP-based data; measurement factors; economic factors; Wechselkurs; Kaufkraftparität; Messung; Statistische Methode; Schätzung; Welt